(untitled) (South Dakota, 1991)
The criteria are prepared and intended to assist engineers to establish uniformity of practice in preparing plans and specifications by proving technical information and suggesting limiting values for items upon which an evaluation of such plans and specifications will be made by the reviewing authority.
Keywords: Liquid wastes,Natural resources,Environmental impact analysis,Nước thải lỏng,Phân tích tác động của môi trường,Cơ sở hạ tầng